TRANSFORMASI PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL: TANTANGAN DAN PELUANG DENGAN PENDEKATAN DIGITAL SOCIETY 5.0 - Nurlaela Muna; Luluk Fitriana; Siswanto, Siswanto (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the challenges and opportunities of Islamic religious education in this very modern digital era. The research method used is qualitative literature or library research. All sources obtained by researchers are literature reviews. Therefore, the data sources are divided into two, namely primary and secondary. Researchers use relevant literature regarding Islamic religious education in the digital era. This research states that the transformative rules of Islamic religious education must be based on monotheism. Tawhid must be deeply instilled in the human heart, because tawhid is what directs all kinds of human life. Islamic religious education in the digital era offers challenges and opportunities by applying interactive learning ideas through relevant theories. It is hoped that the results of this research can provide contributions and strategies regarding adaptive Islamic religious education policies in accordance with the rules of monotheism with a digital society 5.0 approach.